2013
DOI: 10.3390/molecules18032663
|View full text |Cite
|
Sign up to set email alerts
|

Grewia asiatica L., a Food Plant with Multiple Uses

Abstract: Grewia asiatica L., is a species native to south Asia from Pakistan, east to Cambodia, cultivated primarily for its edible fruit and well-reputed for its diverse medicinal uses. Fruits are a rich source of nutrients such as proteins, amino acids, vitamins, and minerals and contain various bioactive compounds, like anthocyanins, tannins, phenolics and flavonoids. Different parts of this plant possess different pharmacological properties. Leaves have antimicrobial, anticancer, antiplatelet and antiemetic activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
50
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 22 publications
3
50
0
Order By: Relevance
“…It is estimated that approximately 80% of the population in developing countries rely on traditional medicines for their primary health care [8, 9]. In China, traditional herbal preparations account for 30 to 50% of the medicines consumed [10].…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that approximately 80% of the population in developing countries rely on traditional medicines for their primary health care [8, 9]. In China, traditional herbal preparations account for 30 to 50% of the medicines consumed [10].…”
Section: Introductionmentioning
confidence: 99%
“…Zia‐Ul‐Haq et al . () noted that Grewia asiatica has a high content of antioxidants such as vitamin C, total phenolics, flavonoids, tannins and anthocyanins. In the present study, we observed the effect of edible coatings on the antioxidant content of phalsa.…”
Section: Resultsmentioning
confidence: 99%
“…Its use as an herbal medicine for the treatment of various diseases such as cancer, aging, fever, rheumatism and diabetes is now well established (Zia‐Ul‐Haq et al . ). The fruit is nonclimacteric with extremely short shelf life.…”
Section: Introductionmentioning
confidence: 97%
“…Grewia asiatica L. (Family: Malvaceae) is a plant of medicinal importances though it is cultivated mainly for its fruits (Zia-Ul- Haq et al, 2013). It is commonly known as Phalsa.…”
Section: Introductionmentioning
confidence: 99%